2011
DOI: 10.1097/yct.0b013e3181eb309e
|View full text |Cite
|
Sign up to set email alerts
|

Electroconvulsive Therapy Training and Confidence in Administration

Abstract: : Our findings indicate deficiencies in training and supervision, which is reflected in the proportion of trainees reporting nil or minimal confidence in their ability to administer ECT. Greater collaboration between training scheme coordinators, clinical tutors, and the College of Psychiatry of Ireland is essential to ensure ongoing monitoring and implementation of standards.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…This could reduce the ability of the current and future generations of caregivers, endanger patient safety, and ultimately increase the risk of ECTrelated complications (12). Several studies have expressed concerns about the obvious weaknesses in the field of skills, competence, and supervision in ECT (13,14). Therefore, this study aimed to find a method to enhance the skill and competence of ECT caregivers.…”
Section: Introductionmentioning
confidence: 99%
“…This could reduce the ability of the current and future generations of caregivers, endanger patient safety, and ultimately increase the risk of ECTrelated complications (12). Several studies have expressed concerns about the obvious weaknesses in the field of skills, competence, and supervision in ECT (13,14). Therefore, this study aimed to find a method to enhance the skill and competence of ECT caregivers.…”
Section: Introductionmentioning
confidence: 99%
“…[1] A survey on psychiatric trainees revealed that inadequate training and supervision resulted in lower confidence and lesser ability to administer ECT in clinical settings. [2] This observation can be extended to the areas of other brain-stimulation techniques in India, given the lack of focused training programs on advanced brain-stimulation applications.…”
mentioning
confidence: 99%